Local Wisdom Instructional Supervision: Enhancing Professionalism of Secondary School Principal in West Nusa Tenggara, Indonesia - Roeslan (International Journal of Advanced Science and Technology, 2020)
This research was aimed at exploring and describing instructional supervision of  high school headmasters based on the local wisdom to enhance teachers’ professionalism. This research employed qualitative approach with multisites study design by using modified inductive analysis.  Three sites were taken including  The first State High School in Bima, The first state high school in Bolo, and the first state high school in Dompu. Data were collected by observation, interview, and documentation. Samples were taken by purposive sampling using snowballing technique. Data were analised using interactive analysis and modified inductive analysis. Results of this research revelealed: 1) the supervision process was carried out using supervision techniques such as: class visits, inservice education and training, teacher / employee meetings, team-teaching, as well as clinical and artistic approaches. 2) Teacher's response to the implementation of supervision; (a) proper guidance by principals fosters commitment and motivation of teachers to do their best, and (b) their awareness of the importance of supervision based on the values ​​of local wisdom. 3) Constraints, difficulties encountered in implementing supervision, namely (a) teaching load; (b) time constraints of school principals and teachers; (c) funding, its role is very supportive in the implementation of teaching supervision; (d) commitment, and (e) feelings of seniority, and 4) Improvement of teacher professionalism is characterized by: (a) teacher competency increases in the improvement of the learning situation, (b) teacher performance increases in the task discipline, learning planning and fosters high initiative and spirit of service and is seen from the behavior and language of principals and teachers who based on local wisdom values ​​from the regional motto of Bima / Dompu (ededu ndai sura dou labo dana, maja labo dahu and nggahi rawi pahu) through example, discipline, diligence, diligence.